Mixed Reality for Virtual Jewellery Fitting - Cheng, Vincent W. S.; Choi, S. H.; Cheung, H. H. (Journal of Marketing Development and Competitiveness, 2019)
The Hong Kong jewellery industry is facing challenges in adopting e-commerce, especially for product visualisation, personalised marketing, and building customer faith. To tackle these challenges, a mixed reality for virtual jewellery fitting (MRVJF) system is developed for jewellery retailing. The MRVJF is designed and implemented in consideration of time and budget limitations, availability of functionalities, and potential benefits. It incorporates mixed reality, face recognition, and hand recognition technologies to improve jewellery visualisation and user-friendliness with interactive virtual fitting on smartphones. The MRVJF is aimed to increase the competitiveness of the Hong Kong jewellery retailers in the global commodity chain.